Extracellular Vesicles Derived from Fermented Soybean (Glycine max) as a Platform for Targeted Drug Delivery in Colorectal Cancer: Isolation, Characterization, and In Vitro/In Vivo Evaluation - Rolef Rumondor; Abid Indra; Sonya Afrilla (Science Journal Get Press, 2026)
Plant-derived extracellular vesicles (PDEVs) are promising nanocarriers for drug delivery, but their therapeutic performance is often limited by low bioactivity and targeting efficiency. This study developed a fermentation-engineered strategy to enhance soybean-derived extracellular vesicles using Lactobacillus plantarum. Fermented soybean EVs (FSE-EVs) were isolated and characterized through nanoparticle tracking analysis, transmission electron microscopy, and high-performance liquid chromatography (HPLC). Drug loading efficiency, pH-responsive release, and anticancer activity were evaluated in colorectal cancer (CRC) cell lines and xenograft mouse models. FSE-EVs showed smaller particle size, improved stability, and a 78% increase in miRNA cargo diversity compared to non-fermented EVs. HPLC analysis demonstrated high 5-fluorouracil (5-FU) encapsulation efficiency (78.3%) and controlled drug release under acidic conditions. Functionally, FSE-EVs loaded with 5-FU significantly enhanced anticancer activity, reducing IC50 values and increasing apoptosis in CRC cells. In vivo, the treatment achieved 83% tumor suppression with minimal systemic toxicity. These findings demonstrate that fermentation can transform PDEVs into an effective, scalable, and food-grade nanoplatform for gastrointestinal cancer therapy.